Controlled wet chemical synthesis of gold nanorods for triclopyr butotyl herbicide detection based-plasmonic sensor - Nur Zehan An'Nisa; Marlia Morsin; Rahmat Sanudin; Nur Liyana Razali; Suratun Nafisah (Sensing and Bio-Sensing Research, 2020)
Gold nanorods (GNRs) have a unique optical property of metallic nanoparticles due to the localised surface plasmon resonance (LSPR) effect, which depends on the size, shape and dielectric property of the surrounding medium. Anisotropic GNRs optical behaviours are approximated based on Mie-Gans theory by predicting the presence of dual absorption bands, which are the transverse and longitudinal bands. This study discussed the investigation of the GNRs formation by controlling three process parameters; centrifugation speed, seed solution concentration and growth solution ageing period to overcome the limitations of rod-shaped nanoparticles due to inhomogeneity, uncontrollable shape and aspect ratio. Bottom-up synthesis has been used to produce fine-tuning gold nanostructures. High yield and aspect ratio of GNRs are achieved at 20 h with 10 μl seed solution concentration and 5000 rpm centrifugation speed for particles separation; a longer growth ageing period caused the uncontrollable formation of GNRs with stacking nanoparticles. Therefore, the optimized GNRs with an aspect ratio of 4.23 ± 0.36 and the yields 74.81% are used as sensing material to detect the targeted herbicide analyte, namely triclopyr butotyl. The concentration of triclopyr butotyl can be detected as low as 3% ~ 1.03 mg/l using the sensing mechanism that was based on the plasmonic effect; which was resulting from the collective oscillations of conduction band electrons in a rod nanoparticle.